UJI RESIDU ANTIBIOTIK PADA DAGING AYAM BROILER YANG DIJUAL DI PASAR MODERN - Siswatiana Rahim Taha; Tri Ananda Erwin Nugroho; Srisukmawati Zainudin; Nansi Yani (xxxx-xxxx, 2022)
The purpose of this study was to identify antibiotic residues in broiler chicken sold in the Gorontalo market, including Sentral Market, Shoping market, Gelael, and Hypermart. This study employed the agar diffusion test method and used 24 samples, namely 12 meat samples and 12 chicken liver samples. The data obtained were analyzed descriptively. The test results showed zero formation of an inhibition zone in the area around the disc paper of each sample. All in all, the chicken sold in the Gorontalo market does not contain antibiotic residues